Feminism and voluntary action - Mahood, Linda (New York : Palgrave Macmillan, 2009)
"Eglantyne Jebb was a teacher, social investigator and founder of the Save the Children Fund. Her "Declaration of the Rights of the Child," adopted by League of Nations, shows evolution from Charity Organization Society model to philosophy of international mutual responsibility, childrens rights and humanitarianism"--Provided by publisher.
Keywords: Child welfare workers; Children's rights; Feminism; Voluntarism